PENGARUH MOTIVASI KERJA DAN KESEJAHTERAAN TERHADAP KINERJA KARYAWAN ADMINISTRASI DI RUMAH SAKIT UMUM DAERAH DR. SOEHADI PRIJONEGORO KABUPATEN SRAGEN DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING - Y. Djoko Suseno, Agung Wijayanto, Amin Wahyudi & (JURNAL MANAJEMEN SUMBER DAYA MANUSIA, 2017)
The purpose of this study is to analyze the influence of work motivationand welfare to the performance either directly or indirectly through jobsatisfaction at the administrative staff at the Regional General Hospital(RSUD) dr. Soehadi Prijonegoro Sragen Regency. This research takes placeat the Regional General Hospital (RSUD) dr. Soehadi Prijonegoro Sragenregency with research variables of work motivation, welfare, job satisfactionand performance. The population that exist in this research is alladministrative employees at the RSUD dr. Soehadi Prijonegoro Sragenregency which amounted to 198 with the sample number 50 respondents.Data collection in this study using questionnaires and documentation. Dataanalysis technique used is path analysis. The results of research workmotivation and welfare affect the performance either directly or indirectlythrough job satisfaction at the administrative staff at the RSUD dr. SoehadiPrijonegoro Sragen Regency.Keywords: work motivation, welfare, job satisfaction, performance.